CSIG-27. MODULATION OF GPR133 (ADGRD1) SIGNALING BY ITS INTRACELLULAR INTERACTION PARTNER EXTENDED SYNAPTOTAGMIN 1 (ESYT1). (14th November 2022) - Stephan, Gabriele; Erdjument-Bromage, Hediye; Liu, Wenke; Frenster, Joshua; Neubert, Tomas; Fenyo, David; Placantonakis, Dimitris
Abstract: GPR133 (ADGRD1), a member of the adhesion GPCR (aGPCR) family, has been recently implicated in the pathogenesis of glioblastoma. Like other aGPCRs, GPR133 is characterized by a large N-terminus, which possesses a conserved GPCR autoproteolysis-inducing (GAIN) domain catalyzing cleavage at a GPCR proteolysis site (GPS), resulting in a C-terminal fragment (CTF) and an N-terminal fragment (NTF). We showed that dissociation of the cleaved NTF and CTF at the plasma membrane correlates with increased GPR133 signaling, which is mediated by coupling to Gs and increase in cytosolic cAMP. Since GPR133 is absent in normal brain cells and de novo expressed in GBM, it represents a potential target for GBM treatment. However, little is known about the receptor's protein interactome and its effects on receptor function and signaling. To identify intracellular interactors of GPR133, we used a proximity biotinylation/mass spectrometry approach in HEK293T cells expressing the wild-type or a signaling-incompetent mutant GPR133. We identified Extended Synaptotagmin 1 (ESYT1), a protein responsible for Ca 2+ -dependent formation of endoplasmic reticulum-plasma membrane bridges, as the strongest interaction partner for both versions of the receptor. Co-immunoprecipitation confirmed robust binding of ESYT1 to GPR133. Knockdown/knockout of ESYT1 increased GPR133 signaling, while overexpression of ESYT1 had the opposite effect. This effect was not mediated by changes in GPR133 expression or plasma membrane trafficking. We are currently performing additional studies to elucidate the mechanism whereby ESYT1 modulates GPR133 signaling. Collectively, these data suggest that GPR133 signaling is modulated through a novel cytosolic, signaling-independent interaction with ESYT1.